Support‐Induced Oxidation State of Catalytic Ru Nanoparticles on Carbon Nanofibers that were Doped with Heteroatoms (O, N) for the Decomposition of NH3. Issue 12 (23rd September 2013) - Marco, Yanila; Roldán, Laura; Armenise, Sabino; García‐Bordejé, Enrique
Abstract Ru nanoparticles were supported on monoliths that were coated with variously functionalized carbon nanofibers (CNFs), that is, un‐doped CNFs, CNFs that had been post‐treated with H2O2, and CNFs that had been doped with nitrogen during their growth. The Ru uptake (by equilibrium adsorption) onto N‐doped CNFs was larger compared to that on their un‐doped and O‐doped counterparts. The functionalization of the CNF support did not play a significant role in determining the size of the deposited Ru nanoparticles, but it substantially impacted on the sintering under the reaction conditions and on the electron density of the reduced metal. Among the catalysts on the different CNF supports, Ru on N‐CNF exhibited the highest H2 productivity from ammonia decomposition, which pointed to electronic effects that were induced by functionalization of the support.